2018
DOI: 10.2478/mgr-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Retail Sprawl in Post-Soviet Urban Residential Communities: Case Studies of Saint-Petersburg and Vilnius

Abstract: Since the beginning of the 1990s, Soviet urban residential communities have experienced rapid inflows of new urban functions. In this research project, two post-Soviet urban areas - Vilnius and St. Petersburg - are examined to indicate contrasting development paths over the last 30 years. The term “retail sprawl” describes correctly one of the important processes which have reshaped the former socialist microdistricts. We used data from the years 1987-1989, the last years of the socialist economy, and 2016 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…These effects are illustrated by At the same time post-industrial transition had minor effect upon commercialization in residential communities, while shift towards "consumption society" was of primary importance there. As for the described "path-dependent" factors, Socialist policy of uniform "microrayon" planning has produced the unique starting ground for monofunctional residential areas with dense night time population and being almost uninhabited during work day time, and with very limited number of retail deliveries (Axenov, Krupickaitė, Morachevskaya, & Zinovyev, 2018). Specificity was added by the very fast pace of post-Second World War redevelopment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects are illustrated by At the same time post-industrial transition had minor effect upon commercialization in residential communities, while shift towards "consumption society" was of primary importance there. As for the described "path-dependent" factors, Socialist policy of uniform "microrayon" planning has produced the unique starting ground for monofunctional residential areas with dense night time population and being almost uninhabited during work day time, and with very limited number of retail deliveries (Axenov, Krupickaitė, Morachevskaya, & Zinovyev, 2018). Specificity was added by the very fast pace of post-Second World War redevelopment.…”
Section: Resultsmentioning
confidence: 99%
“…patterns (Axenov et al, 2018). Absence of pre-planned commercial real estate floor area there contributed to a great extent to the specific outcomes of this process by the spreading of mobile trade forms as well as by specific conversion of the ground floors of the standardized multistoryed purely residential buildings into commercial ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Čas a priestor zohrávajú esenciálnu úlohu pri výskume maloobchodu a spotreby a sú príznačné pre geografický prístup (cf. Axenov et al, 2018, Mulíček, Osman, 2018.…”
Section: úVodunclassified
“…In particular, we will mention the study by Aksenov et al (2006) on the transformation of the city's urban space in 1989-2002. Some scholars focused on the development of industry and tertiary sector in St. Petersburg addressing their impact on the urban environment (Aksenov et al 2001(Aksenov et al , 2016(Aksenov et al , 2018Bater 1980;Bater et al 2000). They demonstrated that the transformations that took place in the post-Soviet period influenced not only the architecture and topography of St. Petersburg but also the socio-geographical makeup of the population, by means of -among everything elsealtering the placement parameters of various social groups.…”
Section: Introductionmentioning
confidence: 99%